Metagenomic analysis reveals potential interactions in an artificial coculture - Minglei Ren; Guiying Zhang; Zi Ye; Zhixian Qiao; Meili Xie; Yan Lin; Tao Li; Jindong Zhao (AMB Express, 2017)
Abstract Disentangling the interactions between cyanobacteria and associated bacterial community is important for understanding the mechanisms that mediate the formation of cyanobacterial blooms in freshwater ecosystems. Despite the fact that a metagenomic approach enables researchers to profile the structure of microbial communities associated with cyanobacteria, reconstructing genome sequences for all members remains inefficient, due to the inherent enormous microbial diversity. Here, we have established a stable coculture system under high salinity, originally from a mixture of an axenic cyanobacterium Synechococcus sp. PCC 7002 and a non-axenic bloom-forming cyanobacterium Microcystis colony. Metagenomic analysis showed that the coculture consists of S. sp. PCC 7002 and two heterotrophic bacteria, designated as Pseudomonas stutzeri TAIHU and Mesorhizobium sp. TAIHU, respectively. And near-complete genome sequences of both bacteria were reconstructed from the metagenomic dataset with an average completeness of 99.8%. Genome-wide pathway analysis revealed that M. sp. TAIHU carried all the genes involved in the de novo biosynthesis of cobalamin, which is required by S. sp. PCC 7002 for growth. To cope with the high salinity in the coculture, experimental evidence demonstrated that S. sp. PCC 7002 would synthesize the compatible solutes including sucrose and glucosylglycerol, which are supposed to be exploited by both heterotrophic bacteria as potential carbon and/or nitrogen sources. Furthermore, the genes encoding for the biosynthesis of the ectoine, another common osmolyte are found exclusively in P. stutzeri TAIHU, while the genes responsible for the catabolism of ectoine and its derives are present only in M. sp. TAIHU. These genomic evidence indicates beneficial interaction between three members in the coculture. Establishment of the coculture system with relative simplicity provides a useful model system for investigating the interspecies interactions, and genome sequences of both bacteria associated with Microcystis bloom described here will facilitate the researcher to elucidate the role of these heterotrophic bacteria in the formation and maintenance of cyanobacterial bloom in freshwater ecosystem.